2015
DOI: 10.1159/000381222
|View full text |Cite
|
Sign up to set email alerts
|

Discontinuous versus Continuous Weaning in Stroke Patients

Abstract: Background: An increasing number of stroke patients have to be supported by mechanical ventilation in intensive care units (ICU), with a relevant proportion of them requiring gradual withdrawal from a respirator. To date, weaning studies have focused merely on mixed patient groups, COPD patients or patients after cardiac surgery. Therefore, the best weaning strategy for stroke patients remains to be determined. Methods: Here, we designed a prospective randomized controlled study comparing adaptive support vent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…On the other hand, BI patients are traditionally ventilated with high VT, on the basis of the observation that hypocapnia reduces ICP, and in order to maintain normal ICP [ 10 ]. However, hyperventilation and the resulting hypocapnia can be detrimental for BI patients, especially during the first 24 h after the initiation of the event, when cerebral homeostasis is critically impaired [ 93 , 94 ]. As previously discussed, MV with high VT could induce further brain and lung injury (i.e., “second hit”) and extracranial organ failure [ 7 ].…”
Section: Ventilatory Strategies In Acute Brain Injury: What Is Different?mentioning
confidence: 99%
“…On the other hand, BI patients are traditionally ventilated with high VT, on the basis of the observation that hypocapnia reduces ICP, and in order to maintain normal ICP [ 10 ]. However, hyperventilation and the resulting hypocapnia can be detrimental for BI patients, especially during the first 24 h after the initiation of the event, when cerebral homeostasis is critically impaired [ 93 , 94 ]. As previously discussed, MV with high VT could induce further brain and lung injury (i.e., “second hit”) and extracranial organ failure [ 7 ].…”
Section: Ventilatory Strategies In Acute Brain Injury: What Is Different?mentioning
confidence: 99%
“…According to the Brain Trauma Foundation Guidelines (18), prolonged prophylactic hyperventilation with PaCO 2 of <25 mmHg is not recommended as first line therapy to reduce ICP, and hyperventilation should be avoided during the first 24 hours after injury when cerebral blood flow (CBF) is often critically reduced. Hyperventilation can be detrimental, as severe hypocapnia and consequent cerebral vasoconstriction can determine brain tissue hypoxia and compromise compliance and blood flow velocities (30,31); (14), as it has been shown that the proportion of induced ARDS increases with the higher initial TV, in particular with mean TV ≥10 mL/Kg (14). All in, when ARDS and TBI coexist, a balance needs to be found between CO 2 control and lung protection.…”
Section: Paco 2 and Tvmentioning
confidence: 99%
“…38 In a small randomized pilot study in ventilated patients with severe stroke, patients weaned by a gradual (continuous) weaning method had a shorter duration of ventilation. 39 It may be reasonable to try SBTs in patients fulfilling the general criteria allowing these (see later), but refrain from further SBTs if they are accompanied by ICP crises or other physiological derangements, and in that case, it might be best to change to a continuous weaning method. In a subgroup of NICU patients, such as those with advanced ALS or extensive brain stem injury, weaning will not be successful.…”
Section: Weaningmentioning
confidence: 99%